Women leadership styles on manufacturing industry employees’ job performance: Evidence from Sarawak, Malaysia - Ting, Pan Wen; Lo, May Chiun; Abang, Azlan Mohamad; Thong, Jun Zhou (Inderscience Enterprises Ltd., 2025)
The under-representation of women in top management is due to various factors, including discriminatory attitudes and family responsibilities. Despite progress, there is still a substantial gap to close, and Malaysia aims to involve 30% of women in top management. The study aims to investigate women's leadership in enhancing employees' job performance. The research aims to examine the relationship between transformational and transactional leadership styles and their effect on job performance in the manufacturing industry of Sarawak. The researchers used Smart PLS 3.0 to analyse the variables of transformational and transactional leadership (idealised influence, inspiration motivation, intellectual stimulation, individual consideration, contingency reward, active and passive management by exception) on job performance. The study revealed that idealised influence and individualised consideration did not have a significant impact on employee performance. However, other dimensions of transformational and transactional leadership had a positive association with job performance.